Peran Teknologi Informasi terhadap Pembukuan Digital pada UMKM - Nuke Virla Wimanda; Shelomita Nadya Pratama; Aisah Putri Panggar Besi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The development of Micro, Small and Medium Enterprises (UMKM) in Indonesia contributes to the expected progress of the Indonesian economy. However, UMKM still face many challenges in the field of accounting and financial reporting. Financial reports are a tool used to determine the value and performance of UMKM. The purpose of this article is to examine the use of technology, especially in the field of accounting and understand the role of accounting information systems in UMKM and the application of digital accounting in UMKM. The method used is a case study method using related journals. The results obtained show that the use of technology in UMKM currently brings digitalization to their activities. For example sales transactions and payment transactions. However, many UMKM still use manual paper accounting. With increasing socialization and rapid technological advances, it is hoped that UMKM players can carry out accounting effectively and efficiently in their businesses so as to create technology-literate UMKM.